European vacation [videorecording (DVD)] - Heckerling, Amy; Chase, Chevy; D'Angelo, Beverly; Hill, Dana, 1964-1996; Lively, Jason, 1968-; Lanoux, Victor, 1936-; Idle, Eric (Warner Home Video, 2002)
The all-American Clark family wins a deluxe European vacation tour. Ecstatic Mr. Clark (who seems to have O.D.'d on "Father Knows Best" reruns) plans a getaway jammed with forced family togetherness, two weeks sure to become a treasure trove of golden Griswald memories. For the Griswalds, it's typical holiday road havoc.